Adaptive Immune Response Stimulation on Nephrolithiasis Mice Model after Treatment of Tempuyung (Sonchus arvensis L.) Leaf Extract - Maghfiroh, Khoirin; Rifa'i, Muhaimin; Widyarti, Sri (The Journal of Experimental Life Science, 2014)
Calcium crystal accumulation on kidney can cause kidney stone (nephrolithiasis). The oxalate calcium crystal which is deposite on the kidney can trigger inflammation on the epithelial that is able to induce cells death (necrosis). The necrosis is able to cause inflammation and it will affect the body's immune system. Infection agent that comes to the body will be responded by the innate immunity which will be responded later by adaptive immunity. One of herbal agent that is expected to be used to stimulate adaptive immunity response is Tempuyung (Sonchus arvensis) leaf extract. The aim of this study is to find out the change of relative amount of CD4+ T cells, CD8+ T cells, and B (B220) cells on nephrolithiasis mice model after S.arvensis leaf extract. The mice are divided into six groups; control group, placebo, nephrolithiasis, S.arvensis leaf extract for 7 days, nephrolithiasis then it is continued with S.arvensis leaf extract for 7 days, and simultaneous (nephrolithiasis and S.arvensis leaf extract for 3 months). The amount of relative T lymphocyte cells is measured by using BD FACSCalibur FlowcytometerTM. The data is analyzed by using ANOVA one way (p<0.05) using SPSS 16.0 software for Windows. The result shows that there are changes of relative CD4+ T cells, CD8+ T cells, and B (B220) cells on nephrolithiasis mice model after the giving of S.arvensis leaf extract. The treatment of S.arvensis leaf extract on the nephrolithiasis mice model can stimulate the homeostatic activity by suppressing the B cells. Compound of S.arvensis leaf extract that can inhibit of Th1 cells and the increase of Th2 cells by proliferation cells activity. The treatment of S.arvensis leaf extract for 7 days can suppress CD4+. The S.arvensis leaf extract can stimulate adaptive immune response which is caused by immunomodulatory active component.Keywords: Nephrolithiasis, Sonchus arvensis L., leaf extract, adaptive immune response.